2008
DOI: 10.1164/rccm.200702-238oc
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia Induces Early Functional Cardiovascular Remodeling in Mice

Abstract: Intermittent hypoxia induces sequential cardiovascular events suggesting increased chemoreflex and depressed baroreflex, resulting in sympathoadrenal hyperactivity, early hemodynamic alterations with proximal histologic remodeling, and delayed changes in peripheral vasoreactivity. Such early alterations before overt cardiovascular disease strengthen the need for identifying at-risk individuals for systematic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(145 citation statements)
references
References 31 publications
11
129
1
4
Order By: Relevance
“…However, there is good evidence that equivalence exists between the two measures of OSAS severity [49], and indeed ODI is at least as reproducible as the AHI between repeated nights [50]. Furthermore, oscillations in oxygen levels may be more pertinent to the vascular effects of OSA than apnoeic events [51] and therefore the current authors believe that the use of an ODI rather than an AHI does not limit the interpretation of their data.…”
Section: Study Limitationsmentioning
confidence: 82%
“…However, there is good evidence that equivalence exists between the two measures of OSAS severity [49], and indeed ODI is at least as reproducible as the AHI between repeated nights [50]. Furthermore, oscillations in oxygen levels may be more pertinent to the vascular effects of OSA than apnoeic events [51] and therefore the current authors believe that the use of an ODI rather than an AHI does not limit the interpretation of their data.…”
Section: Study Limitationsmentioning
confidence: 82%
“…An experimental study using mice suggested that chronic intermittent hypoxia itself induces sympathetic hyperactivation, and thus increases HR. 25 Ziegler et al, 23 showed that CPAP treatment for 10 days lowered daytime HR, as well as plasma and urine noradrenaline. In another study, 26 CPAP treatment for 3-4 days also reduced HR in OSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using animal models 15,24 and also applying IH in healthy humans 25 suggest that IH is a major factor determining blood pressure increase. We have previously shown in C57BL6 mice that blood pressure surges appear at each hypoxic episode, and are associated with increased sympathetic activation 14 . These hemodynamic changes are well known to induce functional and structural alterations of the vascular wall that could contribute to vascular remodeling and atherogenesis 15,26 .…”
Section: Blood Pressure Alterations Due To Ihmentioning
confidence: 93%
“…However, it is well established that atherosclerosis is a chronic inflammatory disease 13 , and there is growing evidence that OSA is a chronic low grade inflammation. Therefore, IH-induced inflammation could be an additional link between OSA and atherosclerosis 9 , without the use of a dyslipidemic diet and even after a short-term of IH exposure, as we previously showed that 14 days of IH were sufficient to induce vascular alterations 14,15 .…”
Section: Introductionmentioning
confidence: 89%